Ion release and physical properties of CPP-ACP modified GIC in acid solutions - Zalizniak, I; Palamara, J E A; Wong, R H K; Cochrane, N J; Burrow, M F; Reynolds, E C (Journal of dentistry, 2013)
A new glass-ionomer cement (GIC) (Fuji VII™ EP) includes 3% (w/w) casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) to enhance ion release. To assess this new GIC compared with a GIC without CPP-ACP (Fuji VII™) with respect to ion release, changes in surface hardness and in mass under a variety of acidic and neutral conditions. Eighty blocks of Fuji VII™ (F7) and Fuji VII™ EP (F7EP) were subjected to three acidic solutions (lactic and citric acids pH 5.0, hydrochloric acid pH 2.0) and water (pH 6.9) over a three-day period. Ion release, surface hardness and weight measurements were carried out every 24h. Higher calcium ion release from F7EP was observed under all acidic conditions. Increased inorganic phosphate ion release was observed for F7EP in hydrochloric and citric acids. Fluoride ion release was similar between F7 and F7EP under all conditions but was significantly higher in acids compared with water. After three days there was no significant difference in surface hardness (p>0.05) between the two materials under all conditions except hydrochloric acid. Minimal change in mass was observed for F7 and F7EP in water, lactic and hydrochloric acids, however citric acid caused significantly more mass loss compared with water (p<0.001). Incorporation of 3% (w/w) CPP-ACP into F7 enhanced calcium and phosphate ion release, with no significant change in fluoride ion release and no adverse effects on surface hardness or change in mass. GICs have the potential to release fluoride ions particularly under acidic conditions associated with dental caries and erosion. A new GIC containing CPP-ACP and fluoride releases not only fluoride ions but also calcium and phosphate ions under acidic conditions which should help to inhibit demineralisation associated with caries and erosion.